Healthcare professionals' perspectives on infant feeding support in paediatric inpatients: single-centre qualitative study - Elizabeth Evans; Bronia Arnott; Rosie Baker; Amy Fielden (BMJ Publishing Group, 2021)
Objective To provide information on baseline knowledge, skills and attitudes (KSA) of paediatric staff to formulate a plan for improving infant feeding support in hospitals.Design Semistructured interviews assessed baseline infant feeding KSA and experiences in 14 paediatric health professionals of various grades (medical students, healthcare assistants, ward nurses and specialist nurses). Audio recordings were transcribed verbatim and underwent thematic analysis. An online questionnaire gathered descriptive statistics about participants.Setting A single large hospital trust, North East England.Results Seven major themes were identified in KSA: culture and trends, roles and working practice, training and resources, the health professional, understanding the parent, effective communication and the challenges of feeding the ill child.Staff discussed various organisational and personal barriers to acquiring infant feeding support training and experience, and to delivering feeding support. Staff were keen to support families with feeding but often felt constrained by a belief that this required specialist knowledge and skills. Although staff believed they actively promoted breastfeeding-friendly messages, it was evident that marketing communications and personal experiences inadvertently influenced their approach to families.Conclusions The development of clear, evidence-based infant feeding education and training for paediatric staff delivered by experienced mentors is warranted. Training should cover background theory, delivering practical support, communication skills and creating a baby-friendly hospital environment. UNICEF Baby Friendly Standards would be suitable to inform content. Training is likely to be received positively by staff and benefit women and babies in this setting.